Examining the effects of teacher self-compassion, emotion regulation, and emotional labor strategies as predictors of teacher resilience in EFL context - Hu, Yan (Frontiers in Psychology, 2023)
Introduction This study investigates the effects of teacher self-compassion, emotion regulation, and emotional labor strategies on teacher resilience in the English as a foreign language (EFL) context. The study aims to understand the relationships between these variables and their potential implications for promoting teacher resilience. Methods A sample of 711 Chinese EFL teachers participated in the study. Confirmatory factor analysis (CFA) was conducted to assess the psychometric properties of the instruments used to measure teacher self-compassion, emotion regulation, emotional labor strategies, and teacher resilience. Structural equation modeling (SEM) was employed to examine the relationships between these variables. Results The results of the study revealed that teacher self-compassion and emotional labor strategies had direct positive effects on teacher resilience. Specifically, higher levels of self-compassion and effective use of emotional labor strategies were associated with greater teacher resilience. Furthermore, teacher emotion regulation was found to indirectly predict teacher resilience through the mediation of emotional labor strategies. This suggests that the ability to regulate emotions influences the adoption of effective emotional labor strategies, which in turn contributes to higher levels of teacher resilience. Discussion The findings of this study highlight the importance of teacher self-compassion, emotion regulation, and emotional labor strategies in promoting teacher resilience in the EFL context. Interventions aimed at enhancing teacher emotional regulation skills and fostering self-compassion may have significant implications for supporting teachers in managing the demands and challenges of their profession, ultimately enhancing their resilience. These findings contribute to the understanding of factors that can promote teacher resilience and inform the development of targeted interventions in the EFL context.